2‐Mercapto Benzoxazole Derivatives as Novel Leads: Urease Inhibition, In Vitro and In Silico Studies. Issue 33 (1st September 2021) - Balogun, Modinat M.; Shamim, Shahbaz; Khan, Khalid M.; Salar, Uzma; Oladosu, Ibrahim A.; Lateef, Mehreen; Wadood, Abdul; Taha, Muhammad; Moronkola, Dorcas O.; Rehman, Ashfaq U.; Rahim, Fazal; Perveen, Shahnaz
Abstract: Twenty‐three benzoxazole derivatives were prepared through two‐step reaction strategy. The precursor, 2‐mercapto benzoxazole was synthesized by reacting 2‐amino phenol with carbon disulfide in the presence of potassium hydroxide. Then, 2‐mercapto benzoxazole was further reacted with substituted phenacyl/benzyl bromide to afford a range of substituted 2‐mercapto benzoxazole analogs. All compounds were characterized by different spectroscopic techniques including mass spectrometry and nuclear magnetic resonance spectroscopy, and investigated against urease enzyme. All analogs revealed good to moderate urease inhibition, ranging from IC50 = 17.50±0.10 to 42.50±0.44 μ M. Few derivatives showed superior activity than thiourea (IC50 =21.50±0.47 μ M), standard inhibitor of urease enzyme. Structure‐activity relationship (SAR) revealed the crucial participation of various structural features in the inhibitory process. Compounds bearing methoxy and halogen substituents were found to show more potency as compared with other molecules. Molecular docking showed various interesting interactions established by molecules (ligand) with the active pocket of urease enzyme. Abstract : A range of benzoxazole derivatives 1 –23 were synthesized in a two‐step reaction strategy and characterized by spectroscopic techniques. All compounds 1 –23 were screened for in vitro urease inhibitory activity. All compounds revealed good to moderate urease inhibition when compared to standard thiourea. Structure‐activity relationship (SAR) shown that compounds bearing methoxy and halogen substituents were found to show good inhibition as compared to other derivatives. Molecular docking studies revealed important interactions between molecules (ligands) and urease enzyme active site.